Lung cancer stage-shift following a symptom awareness campaign - Kennedy, Martyn; Cheyne, Leanne; Darby, Michael; Plant, Paul; Milton, Richard; Robson, Jonathan; Gill, Alison; Malhotra, Puneet; Ashford-Turner, Victoria; Rodger, Kirsty; Paramasivam, Elankumaran; Johnstone, Annette; et al. (BMJ Publishing Group, 2018)
Background: Lung cancer outcomes in the UK are worse than in many other developed nations. Symptom awareness campaigns aim to diagnose patients at an earlier stage to improve cancer outcomes. Methods: An early diagnosis campaign for lung cancer commenced in Leeds, UK in 2011 comprising public and primary-care facing components. Rates of community referral for chest X-ray and lung cancer stage (TNM seventh edition) at presentation were collected from 2008 to 2015. Linear trends were assessed by χ2 test for trend in proportions. Headline figures are presented for the 3 years pre-campaign (2008–2010) and the three most recent years for which data are available during the campaign (2013–2015). Findings: Community-ordered chest X-ray rates per year increased from 18 909 in 2008–2010 to 34 194 in 2013–2015 (80.8% increase). A significant stage shift towards earlier stage lung cancer was seen (χ2(1)=32.2, p<0.0001). There was an 8.8 percentage point increase in the proportion of patients diagnosed with stage I/II lung cancer (26.5% pre-campaign vs 35.3% during campaign) and a 9.3% reduction in the absolute number of patients diagnosed with stage III/IV disease (1254 pre-campaign vs 1137 during campaign). Interpretation: This is the largest described lung cancer stage-shift in association with a symptom awareness campaign. A causal link between the campaign and stage-shift cannot be proven but appears plausible. Limitations of the analysis include a lack of contemporary control population.